Improving the Quality of Education through the Use of Interactive Methods in the Educational Process - Daminov Jakbarali Abduvaliyevich (Journal of Higher Education and Academic Advancement, 2024)
This article presents the possibilities of using the entangled logical chain method to determine the level of education of students when teaching the subject "Structural Mechanics", which is part of the technical disciplines.